Gamification in the improvement of communication skills in primary school students - García Vilca, Marlene Julissa (2024)
Objective. To establish the influence of gamification on the improvement of communication skills in primary school students. Methods. The quantitative approach and design were quasi-experimental. The study involved 80 students divided between the control group and the experimental group. The inferential statistic applied was the Mann-Whitney U test. Results. In the experimental group, 90% of the students in the pretest were at a defcient level, and only 10% were at a regular level. However, after the application of gamification, 78% of the students reached an excellent level, 20% a good level, and only 3% remained at the regular level. The Mann-Whitney U statistic showed a bilateral significance of 0.000. Conclusions. Gamification influences the improvement of communication skills in primary school students; this is because, through gamification, the student interacts with their peers, communicating in different ways with the intention of overcoming the challenges presented by the game.